Differential and Distributional Effects of Energy Efficiency Surveys: Evidence from Electricity Consumption - Thomas J. Kniesner; Galib Rustamov (Institute for the Study of Labor (IZA), 2015)
Our research investigates the magnitude of the effect of residential energy efficiency audit programs on later household electricity consumption. These programs are designed to increase awareness of household energy consumption with personalized feedback that will eventually lead to behavioral changes. In this type of survey, there is only a one-time interaction between households, which participate voluntarily, and the surveyors. The objective of this study is to determine whether and to what extent such surveys lead to behavioral changes. We argue that the perceived complexity of the survey feedback will determine whether the subsequent behavior is sustainable. Then we analyze how persistent the intervention is over time and whether the effects decay or intensify. However, the main evaluation problem involving these surveys is self-selection bias. To correct for this bias, we propose two non-parametric estimators by using a kernel-based propensity score matching approach. In the first method, we use "difference-indifferences" (DID) estimations. The second estimator is quantile DID, which produces estimates on distributions. The comparison group consists of households who were not yet participating in the survey but participated later. The evidence suggest that the customers who participated in the survey reduced their electricity consumption by 6.7%, compared with customers who had not yet participated in the survey. In addition, as the quantiles of the distribution increase, the effect of the program decreases.
Keywords: C31; D03; D12; L94; Q41; 330; electricity consumption; information salience; selection bias; propensity-score matching; treatment effects; multiple treatments